You cannot surge trust: combined naval operations of the Royal Australian Navy, Canadian Navy, Royal Navy, and United States Navy, 1991-2003 - Weir, Gary E; Doyle, Sandra J (Combined naval operations of the Royal Australian Navy, Canadian Navy, Royal Navy, and United States Navy, 1991-2003, 2013)
From the Back Cover: After the Cold War, maritime forces shifted much of their focus from engagements at sea to events ashore. Naval forces were uniquely positioned to influence regional conflicts and to conduct peace support operations called for by the international community-particularly when they cooperated with one another. In this book, naval historians from Australia, Canada, the United Kingdom, and the United States explore how their navies created an effective multinational, or "combined," framework of interoperability while under national rules of engagement. The authors address cases including maritime operations during the First Gulf War (1990-1991) and later (2001-2003) as part of Operation Enduring Freedom; off the Federal Republic of Yugoslavia in Operation Sharp Guard (1991-1996); and in East Timor during Operation Stabilise (1999-2000). This multinational naval force's success in each crisis depended not just on shared doctrine, training, tactics, and technology, but on the trust its sailors built in combined operations over time
Includes bibliographical references and index
Preface: an international city at sea / Gary E. Weir -- Executive summary / Edward J. Marolda -- Introduction: the combined framework: how naval powers deal with military operations other than war / Sarandis Papadopoulos -- The U.S. Navy's role in coalition maritime interception operations in the Persian Gulf region, 1991-2001 / Jeffrey G. Barlow -- Royal Navy operations off the former Yugoslavia: Operation Sharp Guard, 1991-1996 / Stephen Prince and Kate Brett -- The U.S Navy contribution to Operation Sharp Guard / Sarandis Papadopoulos -- The combined naval role in East Timor / David Stevens -- A limited commitment to ending civil strife: the U.S. Navy in Operation Stabilise / Sarandis Papadopoulos -- The U.S. Navy's role in coalition maritime interception in Operation Enduring Freedom, 2001-2002 / Jeffrey G. Barlow -- The Canadian Navy, interoperability, and the U.S. Navy-led operations in the Gulf region, 1991-2003 / Robert Caldwell -- Conclusion / Sarandis Papadopoulos
From the Back Cover: After the Cold War, maritime forces shifted much of their focus from engagements at sea to events ashore. Naval forces were uniquely positioned to influence regional conflicts and to conduct peace support operations called for by the international community-particularly when they cooperated with one another. In this book, naval historians from Australia, Canada, the United Kingdom, and the United States explore how their navies created an effective multinational, or "combined," framework of interoperability while under national rules of engagement. The authors address cases including maritime operations during the First Gulf War (1990-1991) and later (2001-2003) as part of Operation Enduring Freedom; off the Federal Republic of Yugoslavia in Operation Sharp Guard (1991-1996); and in East Timor during Operation Stabilise (1999-2000). This multinational naval force's success in each crisis depended not just on shared doctrine, training, tactics, and technology, but on the trust its sailors built in combined operations over time
Keywords: Navies / International cooperation. / fast / (OCoLC)fst01035081; Naval history, Modern. / fast / (OCoLC)fst01035008; Combined operations (Military science) / fast / (OCoLC)fst00868996; Blockade. / fast / (OCoLC)fst00834524; Naval history, Modern / 21st century; Naval history, Modern / 20th century; Combined operations (Military science) / Case studies; Navies / International cooperation / Case studies; Blockade / Case studies; Case studies. / fast / (OCoLC)fst01423765